Soils & Fertilizers for Master Gardeners: Soil Formation in Florida - Amy L. Shober; Thomas A. Obreza (EDIS)
Revised! SL274, a 4-page illustrated fact sheet by Amy L. Shober and Thomas Obreza, provides information about types of soils found in Florida and the factors that influenced their formation. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, January 2009.